2015
DOI: 10.1089/cap.2014.0049
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Adolescents at Highly Elevated Risk for Suicidal Behavior in the Emergency Department

Abstract: In this study, use of a higher screen threshold (multiple suicide risk factors) showed promise for identifying highly elevated acute risk for suicidal behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…Sensitivity and specificity analyses highlight the ability of brief suicide risk screening approaches to identify individuals who will return to the ED for suicide-related reasons, with similar results as other previously published analyses (King, Berona, Czyz, Horwitz, & Gipson, 2015). These analyses underscore the importance of connecting positive responses on these screens to appropriate referrals for treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Sensitivity and specificity analyses highlight the ability of brief suicide risk screening approaches to identify individuals who will return to the ED for suicide-related reasons, with similar results as other previously published analyses (King, Berona, Czyz, Horwitz, & Gipson, 2015). These analyses underscore the importance of connecting positive responses on these screens to appropriate referrals for treatment.…”
Section: Discussionsupporting
confidence: 81%
“…For example, a recent study of adolescents in a general emergency department screened for suicide ideation/attempt, depressive symptoms, and alcohol/substance abuse found that youth endorsing all domains were most likely to engage in suicidal behavior two months later (King et al, 2015; Pena et al, 2012). Impairment due to alcohol/substance abuse may be a marker of a developmental trajectory with pervasive externalizing, disinhibited behavior and captures a group of individuals who are likely to engage in harmful mood-dependent behaviors (Zucker et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The challenge of differentiating who is actually at a high risk for suicidal behavior is especially salient for Emergency Departments (EDs) serving large numbers of individuals presenting with self-inflicted injuries [3,4] and numerous risk factors. These include a study evaluating a multicomponent screening tool administered to adolescents in a general medical ED [7] and two studies [5,8] examining the predictive validity of Columbia-Suicide Severity Rating Scale (C-SSRS) [9] among adolescents and emerging adults seen in a psychiatric ED. [5] While promising suicide risk screening tools-such as the Ask Suicide-Screening Questions (ASQ) [6] -have been developed for youth presenting to EDs and demonstrated strong concurrent validity, there have been relatively few efforts addressing the substantial need for prospectively validated suicide risk assessment tools.…”
Section: Introductionmentioning
confidence: 99%